Analisis Kelayakan Klusterisasi Industri Hasil Hutan Bukan Kayu (HHBK) di Kesatuan Pengelolaan Hutan (KPH) Hulu Sungai - Al Fajar, Muhammad Hatami; Sa’roni, Chairul (PPJP ULM, 2022)
This study aims to determine the potential for cluster analysis of Non-Timber Forest Products (HHBK) in the Upstream River and Non-Timber Forest Products (HHBK) KPHs, which are most suitable for industrial development in the FMU. Sources of data used are primary and secondary data in a Long Term Management Plan (RPHJP) Upstream Forest Management Unit (KPH) document and interviews. The data analysis technique used is a feasibility study to find out what non-timber forest products will be most suitable for industrial development in the FMU Hulu Sungai. The results showed that the FMU Hulu Sungai had potential Non-Timber Forest Products (HHBK), namely Aren, Bamboo, and Candlenut. The use of the feasibility study method to get the priority scale which is the most feasible to be built by industry. Analysis of the Clusterization of Non-Timber Forest Products Industry (HHBK) in the Hulu Sungai FMU can be used as a reference for the industry office and Forest Management Units (KPH) to see whether or not an industry should be built in the FMU Hulu Sungai